A PROPOSED TRAINING PROGRAM FOR EMPLOYING CHATGPT ARTIFICIAL INTELLIGENCE APPLICATIONS FOR FACULTY MEMBERS AT THE UNIVERSITY OF JORDAN BASED ON CONNECTIONIST THEORY - Faten Abdalkareem Alsmadi (Indonesian Journal of Education (INJOE), 2026)
This study aimed to design a proposed training program based on connectivist theory for employing artificial intelligence applications (ChatGPT) among faculty members at the University of Jordan. The study adopted a mixed-methods approach, including a quantitative analysis through a questionnaire administered to 332 faculty members, and a qualitative analysis through interviews with 15 faculty members to identify the standard specifications of the program. The results indicated that the majority of faculty members emphasized the importance of formulating clear, applicable, and measurable general and specific objectives (93.5%), identifying the target group and its training needs (80%), and ensuring continuous assessment and feedback (80%). The primary goals of the program identified as developing research skills, improving the educational process, and empowering learning (66.7%). Participants also highlighted that the training program should be flexible, have content aligned with trainees’ skills and needs, enhance interaction and participation, and promote critical thinking and problem solving. The program should focus on developing research, communication, and collaboration skills to keep pace with technological advancements. Furthermore, the study stressed the importance of integrating social, cultural, and ethical standards to ensure the program’s effectiveness and sustainability. The study recommended designing training content that encourages active and interactive learning, formulating clear and specific objectives, creating a flexible learning environment using technology and AI tools, and implementing continuous evaluation to collect feedback and improve program effectiveness.